1993
DOI: 10.1136/pgmj.69.807.37
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory and analgesic action of transdermal glyceryltrinitrate in the treatment of infusion-related thrombophlebitis

Abstract: Summary:We have carried out a prospective double-blind randomized study in 40 patients with infusion-related thrombophlebitis. Twenty-two patients were included in the glyceryltrinitrate (GTN) ointment group and 18 patients in the control heparinoid group. Pain was assessed by an analogue scale. At 48 hours the analgesic index was 84.6 ± 18 units with GTN and 49 ± 45 units with heparinoid ointment (P <0.01). Faster relief of oedema was also observed in the GTN-treated group. All signs of thrombophlebitis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 20 publications
0
11
2
Order By: Relevance
“…NTG was found to be useful for the treatment of shoulder pain (17) and thrombophlebitis (7,18) and for enhancing the effect of spinal sufentanil or neostigmine (6,19). Lauretti et al (5) also showed that delivery of NO donors (transdermal NTG) together with opioids may be of significant benefit in cancer pain management, delaying morphine tolerance and decreasing the frequency of adverse effects related to large doses of opioid.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…NTG was found to be useful for the treatment of shoulder pain (17) and thrombophlebitis (7,18) and for enhancing the effect of spinal sufentanil or neostigmine (6,19). Lauretti et al (5) also showed that delivery of NO donors (transdermal NTG) together with opioids may be of significant benefit in cancer pain management, delaying morphine tolerance and decreasing the frequency of adverse effects related to large doses of opioid.…”
Section: Discussionmentioning
confidence: 96%
“…Lauretti et al (5) also showed that delivery of NO donors (transdermal NTG) together with opioids may be of significant benefit in cancer pain management, delaying morphine tolerance and decreasing the frequency of adverse effects related to large doses of opioid. Data from the literature suggest that in humans, large doses of transdermal NTG, such as 30 mg daily, are hyperalgesic, whereas doses Ͻ6 mg daily are analgesic under various circumstances (17)(18)(19). Because of these data, we chose to add small dose (200 g) NTG to lidocaine for an analgesic effect.…”
Section: Discussionmentioning
confidence: 97%
“…This suggestion is in line w ith the observations that NO donors are either e ffec tive as analgesic s by themselves or in c onjunction w ith other analgesics. [29][30][31][32] In conclusion, the pre sent study confirms that L-NAME c ause s analgesia and de monstrate d that L-NMMA, another NO synthase inhibito r, signific antly blocked both the peripheral and c entral antino cice ptive actions of L-NAME in rats and mic e. L-NAME antino cic eption w as also blocke d by inhibito rs of guanilate-c yclase activation and pote ntiate d by arginine and by a cGMP phosphodie ste ras e inhibitor. These re sults allow us to spe culate that L-NAME causes antino cic eption by ac ting as a partial agonist, thus stimulating iNOS ac tivation in the nocice ptive te sts use d. Furthermore our results draw into que stion the use of L-NAME alone as a me thodological tool to charac te rise the nocic eptive role of the arginine -NO-cGMP pathw ay in physiopathological proc esses, in the absenc e of confirmatio n w ith anothe r NO synthase inhibito r.…”
Section: Mediators Of Inflammation · Vol 9 · 2000mentioning
confidence: 99%
“…[1][2][3][4]29] NTG may possibly cause dose-dependent side effects such as hypotension, tachycardia or headache as well. [27] In the present study, there was no significant difference in side effects between groups.…”
mentioning
confidence: 54%
“…[22,23] NTG was found to be beneficial in the treatment of shoulder pain, [24] chronic thoracotomy pain [25] and thrombophlebitis [26] and for augmenting the effect of spinal sufentanil or neostigmine, [27] or epidural S(+)-ketamine. [28] In these investigations, the analgesic effects of transdermal NTG were investigated, while in our study, the efficiency of IV NTG was documented with the mechanism similar to that of transdermal NTG.…”
mentioning
confidence: 99%